STRATEGIC LEADERSHIP AND SUSTAINABILITY: THE ROLE OF CEO CELEBRITY IN PROMOTING GREEN INNOVATION - Chandra, Budi; Ivone; Tanujaya, Kennardi; Surny (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2025)
This study aims to investigate the impact of CEO celebrity status on green innovation (GI) adoption in companies listed on the Indonesia Stock Exchange (IDX) during the period 2018-2022. This study applies empirical analyses to examine the relationship between high-profile leadership and sustainability practices. Regression analyses and robustness tests, including coarsened exact matching (CEM), were used to ensure the validity of the findings. The results show that companies with celebrity CEO celebrity have higher rates of GI adoption compared to companies without CEO celebrity, emphasising the influential role of CEO visibility in advancing corporate sustainability initiatives. The findings support the Upper Echelon Theory (UET) which states that the characteristics of top executives influence strategic decisions. The implication is that companies should utilise the public profile of their leaders to strengthen environmental initiatives and build stakeholder trust. Limitations include the geographical focus on Indonesia and the use of a binary indicator for CEO celebrity status. Future research should look at other markets and use more detailed measurements for a clearer understanding.